Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep38100
|View full text |Cite
|
Sign up to set email alerts
|

A network intervention that locates and intervenes with recently HIV-infected persons: The Transmission Reduction Intervention Project (TRIP)

Abstract: Early treatment, soon after infection, reduces HIV transmissions and benefits patients. The Transmission Reduction Intervention Project (TRIP) evaluated a network intervention to detect individuals recently infected (in the past 6 months). TRIP was conducted in Greece (2013–2015) and focused on drug injector networks. Based on HIV status, testing history, and the results of an assay to detect recent infections, TRIP classified drug injector “Seeds” into groups: Recent Seeds (RS), and Control Seeds with Long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(119 citation statements)
references
References 41 publications
5
102
0
2
Order By: Relevance
“…Furthermore, cost comparisons indicate that TRIP techniques locate PwRI less expensively than does IBBS. These findings support the conclusions of a TRIP‐related study in Athens, Greece , which concluded that “efforts to seek, test, and treat PwRI can be accelerated using strategic, network‐based approaches.” The results in this paper show that, in Odessa, the risk network recruitment approach used in TRIP, together with recruiting seeds who were HIV positive, located more PwRI (at less expense) than a standard RDS epidemiologic study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, cost comparisons indicate that TRIP techniques locate PwRI less expensively than does IBBS. These findings support the conclusions of a TRIP‐related study in Athens, Greece , which concluded that “efforts to seek, test, and treat PwRI can be accelerated using strategic, network‐based approaches.” The results in this paper show that, in Odessa, the risk network recruitment approach used in TRIP, together with recruiting seeds who were HIV positive, located more PwRI (at less expense) than a standard RDS epidemiologic study.…”
Section: Discussionsupporting
confidence: 82%
“…Contrary to our expectations, the two arms of TRIP recruited similar proportions of PwRI in Odessa. In Athens TRIP, the networks of PwRI contained higher proportions of PwRI than did the networks of longer‐term HIV‐positives . These different results may well be due to the different percentages in the two cities of risk network members who were recruited from venues as opposed to from among named risk network members.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, on the largest scales, one can reconstruct networks of interactions among members of a particular species [50][51][52], or different species in an ecosystem [53][54][55][56][57][58]. This knowledge may help in forecasting ecological catastrophes [59,60] and addressing the spread of infectious disease [61] (or other epidemics [62]). …”
Section: Etdq Rkqvmidgsamird Ymrtgegflc Mldf Rkqvvicgysfmifdqymrtgegfmentioning
confidence: 99%